Effects of Body-Oriented Interventions on Preschoolers' Social-Emotional Competence: A Systematic Review - Dias Rodrigues, Andreia; Cruz-Ferreira, Ana; Marmeleira, José; Veiga, Guida (Frontiers in Psychology, 2022)
Objective: A growing body of evidence supports the effectiveness of body-oriented interventions (BOI) in educational contexts, showing positive influences on social-emotional competence. Nevertheless, there is a lack of systematization of the evidence regarding preschool years. This is a two-part systematic review. In this first part, we aim to examine the effects of BOI on preschoolers’ social-emotional competence outcomes. Data sources: Searches were conducted in Pubmed, Scopus, PsycInfo, ERIC, Web of Science, Portal Regional da BVS and CINAHL. Eligibility criteria: English, French and Portuguese language articles published between January 2000 and October 2020, that evaluated the effects of BOI implemented in educational contexts on social-emotional competence of preschool children. Only randomized controlled trials (RCT) or quasi-RCT were included. Data extraction and synthesis: Two reviewers independently completed data extraction and risk-of-bias assessment. The level of scientific evidence was measured through the Best Evidence Synthesis. Results: Nineteen studies were included. There was strong evidence that BOI do not improve anger/aggression, delay of gratification and altruism. Nevertheless, there was moderate evidence that BOI effectively improve other social-emotional outcomes, such as empathy, social interaction, social independence, general internalizing behaviors, and general externalizing behaviors. The lack of scientific evidence was compromised by the methodological quality of the studies. Conclusion: BOI effectively improve specific social-emotional competencies of preschool children.